Identification of a triangular two equation system without instruments - Arthur Lewbel; Susanne M. Schennach; Linqi Zhang (Centre for Microdata Methods and Practice (cemmap), 2020)
We show that a standard linear triangular two equation system can be point identified, without the use of instruments or any other side information. We find that the only case where the model is not point identified is when a latent variable that causes endogeneity is normally distributed. In this non-identified case, we derive the sharp identified set. We apply our results to Acemoglu and Johnson's (2007) model of life expectancy and GDP, obtaining point identification and comparable estimates to theirs, without using their (or any other) instrument.
Keywords: 330